Occupational and personal risk factors for carpal tunnel syndrome in industrial workers - Roquelaure, Yves; Mechali, S.; Dano, C.; Fanello, S.; Benetti, F.; Bureau, D.; Mariel, J.; Martin, Y.-H.; Derriennic, F.; Penneau-Fontbonne, D. (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'The purpose of the study was to evaluate both nonoccupational and occupational factors associated with carpal tunnel syndrome (CTS) in industrial workers. ' ' METHODS ': 'Sixty-five workers with CTS were compared with 65 referents matched for gender, age, and plant. The medical history and household activities of the workers and the ergonomic and organizational characteristics of the job were analyzed. ' ' RESULTS ': 'Exertion of force over 1 kg was associated with CTS [odds ratio (OR) 9.0]. Two risk factors were related to motion repetitiveness: length of the shortest elementary operation of ≤10 s (OR 8.8) and lack of change in tasks or lack of breaks for at least 15% of the daily worktime (OR 6.0). No posture of the upper limb was associated with CTS. Workstation design involving the manual supply of the workers (OR 5.0) and the lack of job rotation (OR 6.3) were associated with CTS. The only personal factor associated with CTS was a parity of at least 3 (OR 3.2). There was a continuous increase in the odds ratio against the number of risk factors accumulated by the workers; the odds ratio thus ranged from 5.6 when 3 of the 6 risk factors were present to ≥90 when 4, 5, or 6 risk factors were accumulated. ' ' CONCLUSION ': 'The results were in agreement with a model for CTS which included 1 personal and 5 occupational risk factors. The number of risk factors cumulated by the workers seems to be a major determinant of CTS.
Keywords: epidemiology; force; job-site analysis; MSD; musculoskeletal disorder; nerve entrapment; repetitiveness